Clarifying the meaning of a positive living environment in nursing homes: A scoping review protocol. - Lien Janssens; Lisa Geyskens; Bernadette Dierckx de Casterlé; Ellen Vlaeyen; Mieke Deschodt (PLoS ONE)
Background Nursing homes provide permanent residence and care for older individuals who can no longer live independently. Despite efforts to create a safe and homelike environment, concerns persist regarding residents' well-being. Current research often focuses on different aspects, such as quality of life, sense of home or thriving in the nursing home, each only providing a partial understanding of what constitutes a positive living environment. To address this, we will explore what entails the concept of 'a positive living environment' in nursing homes from the perspectives of residents, staff, and informal caregivers. Methods We will follow Levac and colleagues' scoping review framework, integrating Walker and Avant's concept analysis methodology. Searches will be conducted in PubMed, Embase, Scopus, Web of Science and CINAHL. We will include peer-reviewed qualitative or mixed-method studies, published in English or Dutch in the last 20 years. Studies must address nursing home settings and explore perspectives of residents, staff, or informal caregivers on what constitutes a positive living environment. Title and abstract screening will be performed by one reviewer, with a second reviewer assessing a subset of papers until reaching a 90% agreement rate. Full-text screening will be conducted by one reviewer, with any doubts discussed with the research team. Forward and backward snowballing techniques will be used on papers that pass full-text screening. Data will be extracted and analyzed using concept analysis methodology by examining uses of the concept, defining attributes, antecedents, consequences, and empirical referents. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews will be used as the reporting guideline. Conclusion This protocol outlines the methods for our scoping review to clarify the concept of a positive living environment in nursing homes. Its findings will guide the development of nursing home environments to better meet residents' needs and preferences.